Family in the life of distinguished scholars. The example of Kazimierz Twardowski (1866–1938) - Szulakiewicz, Władysława (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
Kazimierz Twardowski is considered to be the creator of the Lvov-Warsaw philosophical school. Literature depicts him as an eminent scholar, teacher, organiser of scientific life. The subject of dissertation in this paper is an attempt to answer the following questions:What man was Kazimierz Twardowski like in everyday family life?What place did family occupy in his life?This sketch was prepared on the basis of Kazimierz Twardowski’s Diaries and an interview and conversations with his grandson professor Andrzej Tomczak, as well as the correspondence of K. Twardowski with his student Tadeusz Czeżowski.
Keywords: family; philosopher; teachers; scientific life